HUBUNGAN PRAKTIK PEMBERIAN MAKANAN PENDAMPING ASI (MP-ASI) DENGAN STATUS NUTRISI BAYI USIA 9-12 BULAN - Lisdahartati Br Sinulingga; Riri Novayelinda; Hellena Deli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Inappropriate complementary feeding practice can negatively affect the nutritional intake of infants. It also influences their weight gain. This study aimed to determine the correlation between complementary feeding practice and nutritional status of infants aged 9-12 months in the service area of Puskesmas (Community Health Centre) Sail in Pekanbaru. The research used quantitative approach with descriptive correlative research design. The research instrument used was a questionnaire which has passed validity and reliability test, and KMS (infant’s growth chart) to determine infants’ nutritional status based on their BB/U (weight-for-age). 104 respondents took part in this study. respondents were parents with infants 9-12 years old who to agree to participate in this study. The univariate data showed that most of the respondents had female infants (57.7%) with the majority of those infants aged 9 months (31.7%); the dominant respondents’ education background was high school graduates (54.8%) and in early adult age (67.3%) with housewives as the most common occupation (70.2%). From the questionnaire, 52 respondents (50%) conducted good complementary feeding practice, and 76.9% of the participants’ infants were within the normal body weight range. The result of chi square statistic test showed the p value = 0.001, α < 0.05, meaning that there was a correlation between the complementary feeding practice and nutritional status of infants aged 9-12 months. The result of this study can be the source of information for people and health workers to provide health education on the good practice of complementary feeding.Key words: complementary feeding, nutritional status